Duodenal Adenocarcinoma at the Ligament of Treitz: Management and Outcome - Biello, Andrew R. (Hawaii J Health Soc Welf, 2019)
Primary small bowel neoplasms at the ligament of Treitz are extremely rare and require advanced surgical technique for extirpation. The insidious onset of disease allows for a delayed presentation, often accompanied by moderate-size growth of the neoplasm, causing intestinal bleeding and bowel obstruction. The partial retroperitoneal location of these tumors pose a unique challenge for surgical resection. We present an unusual case of a primary small bowel adenocarcinoma at the Ligament of Treitz, requiring segmental resection of the fourth portion of the duodenum plus the proximal jejunum.